2010
DOI: 10.1113/jphysiol.2009.184168
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modification of fetal baboon hepatic phosphoenolpyruvate carboxykinase following exposure to moderately reduced nutrient availability

Abstract: Decreased maternal nutrient availability during pregnancy induces compensatory fetal metabolic and endocrine responses. Knowledge of cellular changes involved is critical to understanding normal and abnormal development. Several studies in rodents and sheep report increased fetal plasma cortisol and associated increased gluconeogenesis in response to maternal nutrient reduction (MNR) but observations in primates are lacking. We determined MNR effects on fetal liver phosphoenolpyruvate carboxykinase 1 (protein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 43 publications
2
109
0
Order By: Relevance
“…Additional mechanisms mediating the effects of maternal undernutrition on fetal brain development may be secondary to well-known detrimental effects of excess glucocorticoid exposure on the developing central nervous system (16). The same group of investigators has reported that a similar level of maternal undernutrition led to significant elevations in circulating glucocorticoids in the baboon fetus (17).…”
Section: Maternal Undernutrition and The Primate Fetal Brainmentioning
confidence: 89%
“…Additional mechanisms mediating the effects of maternal undernutrition on fetal brain development may be secondary to well-known detrimental effects of excess glucocorticoid exposure on the developing central nervous system (16). The same group of investigators has reported that a similar level of maternal undernutrition led to significant elevations in circulating glucocorticoids in the baboon fetus (17).…”
Section: Maternal Undernutrition and The Primate Fetal Brainmentioning
confidence: 89%
“…This increase was shown to be due to an enhanced activity of PEPCK which results from decreased methylation of the gene's promoter [13]. Formerly, it was assumed that substantial gluconeogenesis only starts to occur` at birth [22], but more recent publications, using mammalian animal models of intrauterine growth restriction and inadequate maternal nutrition, point towards intra-uterine initiation of gluconeogenesis [13,23,24]. In fetal baboons it was shown that the PEPCK protein, a key enzyme in gluconeogenesis, was upregulated in MNR fetuses [13].…”
Section: 9gmentioning
confidence: 99%
“…Metabolic adaptations during development in response to decreased fetal nutrition may persist after birth, even when nutrition has returned to the normal range [12]. For instance, fetuses experiencing MNR have increased phosphoenolpyruvate carboxykinase (PEPCK) activity in the fetal liver, indicating elevated gluconeogenesis [13] and they also have higher fasting glucose levels 3.5 years after birth [11]. The aim of the present study was to explore the effects of MNR in pregnancy on the metabolic signature of fetal baboons.…”
mentioning
confidence: 99%
“…Epigenetic mechanisms, which include direct DNA methylation, posttranslational histone modifications, and microRNAs (miRs), influence the long-term expression of a gene by altering the ability of the transcriptional machinery to interact with the chromatin environment. Elegant studies in the baboon fetus have demonstrated that 70% undernutrition during pregnancy led to augmented hepatic gluconeogenesis associated with both increased Pck1 mRNA and decreases in the methylation of CpG dinucleotides of the Pck1 promoter [59]. Moreover, uterine ligation has been shown to directly increase DNA methylation in the promoter of hepatic Igf-1 at birth and that this persists into the F2 generation even when F1 IUGR offspring are adequately nourished [48,74].…”
Section: Direct Mechanisms Linking Maternal Undernutrition and Adversmentioning
confidence: 99%
“…Moreover, like models of uterine ligation, fetal liver growth from MNR dams is compromised at birth followed by rapid postnatal catch-up growth [36,55,58]. However, with models of MNR, the impact of a decrease in maternal and placental weight during pregnancy must also be taken into consideration [55,59]. Sheep and rat studies have demonstrated that MNR leads to glucose intolerance and insulin insensitivity, along with greater hepatic lipid and glycogen content in the offspring [58,60].…”
Section: Maternal Nutrient Restriction (Mnr) Model Of Undernutritionmentioning
confidence: 99%